The Union Rate of Ankle Arthrodesis Using Double‑column Plating - Salawu, Oni Nasiru; Babalola, O. M.; Ahmed, B. A.; Ibraheem, G. H.; Mejabi, J. O.; Olawepo, A.; Nwosu, C. (Nigerian Journal of Orthopaedics and Trauma, 2020)
Background: Ankle arthrodesis is commonly used for the treatment of end‑stage ankle osteoarthritis. Many methods have been used for ankle arthrodesis with varying outcomes. A sustained rigid fixation which will enhance healing is the goal of all methods of ankle arthrodesis. The required rigid fixation needed for healing is provided by the method of plating described in this report. The aim of this study is to determine the time to clinical union, time to radiological union and the union rate following the use of double‑column plating for arthrodesis of the ankle joint. Methodology: This was a prospective study done at Federal Medical Centre, Birnin Kebbi. All adult patients who had double‑column plating for severe osteoarthritis of the ankle joint from April 2015 to March 2018 were included in the study after obtaining their consent. Results: There were 19 patients in the study, one female and 18 males with the mean age of patients treated as 39.6 ± 8.9 years. All patients had post‑traumatic osteoarthritis, and double‑column plating was used to achieve arthrodesis in all patients. The average time to clinical union was 8.00 ± 0.89 weeks, while the average time to radiological union was 9.75 ± 1.61 weeks. By 6‑month post surgery, the union rate was 100%. The complications noticed were broken screws in one patient and pain in adjacent joints in two patients. Conclusion: The use of double‑column plating for ankle arthrodesis is a useful method with high union rate and low rate of complications. It is a reliable method for closed, non‑infected ankle pathologies that require arthrodesis.